Have Consumption Risks in the G7 Countries Become Diversified? - Nikolaos Antonakakis; Johann Scharler (FIW - Research Centre International Economics, 2011)
This paper studies the dynamics of international consumption risk sharing among the G7 countries. Based on the dynamic conditional correlation model due to Engle (2002), we construct a time-varying, consumption-based measure of risk sharing. We find that although the exposure to countryspecific shocks has declined in the G7 countries, with Japan being an exception, the evolution of risk sharing is rather heterogeneous across countries.
Keywords: E3; F4; 330; Dynamic conditional correlation; consumption risk sharing